Inside Cover: Combined Secondary Ion Mass Spectrometry Depth Profiling and Focused Ion Beam Analysis of Cu Films Electrodeposited under Oscillatory Conditions (ChemElectroChem 5/2015). Issue 5 (13th May 2015) - Hai, Nguyen T. M.; Lechner, David; Stricker, Florian; Furrer, Julien; Broekmann, Peter
<x xml:space="preserve">Abstract</x> The figure shows a Cu wafer that has been processed with an additive package (SPS, Imep). The graph superimposed on the picture shows a characteristic linear‐sweep voltammogram of the Cu deposition process in the presence of these additives. The N‐shaped negative differential resistance is the physical origin of the oscillatory behavior during Cu deposition under galvanostatic conditions as reported by P. Broekmann et al. on p. 664.